Structure and petrology of the Dadeldhura Group, far western Nepal, Himalaya - Næraa, Tomas; Konnerup-Madsen, Jens; Hageskov, Bjørn; Paudel, Lalu Prasad (Journal of Nepal Geological Society, 2007)
The granites, phyllites, schists, and gneisses of the Dadeldhura Group exhibit a significant Himalayan metamorphic imprint. The rocks of the group constitute a synform and the group is delimited by thrusts. The North Dadeldhura Thrust (NDT) zone is dominated by granitic mylonite with subordinate quartzite, quartz-chlorite schist, and amphibolite. In the quartz-chlorite schist from the NDT zone, relict kyanite is observed, which together with recrystallisation textures in the granitic mylonite indicate that low-temperature syn-tectonic retrogression has affected the thrust zone. Prograde garnets with spiral structures from a zone 2–4 km structurally above the base of the NDT are associated with mylonite-like rocks, and indicate distinct prograde shear zones in this area. This suggested that prograde thrust stacking has affected about 4 km wide north belt of the Dadeldhura Group. Rim thermobarometry from the garnet holding rocks shows that the minerals were re-equilibrated at 440–550 °C and 6.5–9.5 kbar. In the southern part of the Dadeldhura Group, textures in quartz and feldspar from the Saukhark Granite-Gneiss indicate that temperatures during recrystallisation were around 450–550 °C. These P–T estimates suggest that most of the now exposed rocks in the Dadeldhura Group experienced prograde epidoteamphibolite facies metamorphism during early orogenic build up and thrusting of the Dadeldhura Nappe. A subsequent syntectonic retrograde phase is observed in the NDT zone as low temperature recrystallisation of quartz and feldspar in mylonitic rocks, and chlorite and quartz in chlorite-grade rocks holding relict kyanite. Retrograde trusting was also focused along a distinct “back thrusting” zone within the northern part of the group.